2017
DOI: 10.1177/1077699016685558
|View full text |Cite
|
Sign up to set email alerts
|

Science in the Social Media Age: Profiles of Science Blog Readers

Abstract: Science blogs have become an increasingly important component of the ecosystem of science news on the Internet. Through a survey of 2,955 readers of 40 randomly selected science blogs, we created profiles of science blog users. Super users indicated reading science blogs for a wide range of reasons, including for community-seeking purposes. One-way entertainment users indicated reading blogs more for entertainment and ambiance. Unique information-seeking users indicated reading blogs more for specific informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 40 publications
3
47
0
1
Order By: Relevance
“…Almost a quarter of AAAS members reported that they have written for a blog (Pew Research Center, 2015). One study found more than half the readers surveyed from a variety of science blogs, including independent and more established network blogs, were over forty years old and one third were over fifty years old, with a 40:60 female-to-male breakdown for those who identified within the categories of female or male (Brown Jarreau, 2016;Jarreau & Porter, 2018). And, although the majority of respondents were educated in the sciences, more than half reported they never blogged about science themselves.…”
Section: Background: Science Blogging and Science Blog Networkmentioning
confidence: 99%
“…Almost a quarter of AAAS members reported that they have written for a blog (Pew Research Center, 2015). One study found more than half the readers surveyed from a variety of science blogs, including independent and more established network blogs, were over forty years old and one third were over fifty years old, with a 40:60 female-to-male breakdown for those who identified within the categories of female or male (Brown Jarreau, 2016;Jarreau & Porter, 2018). And, although the majority of respondents were educated in the sciences, more than half reported they never blogged about science themselves.…”
Section: Background: Science Blogging and Science Blog Networkmentioning
confidence: 99%
“…It is possible that many of those participating in the blog as commenters are scientists or have a technical background, which may not be surprising given the aim of the blog is to convey the science of climate change. Jarreau and Porter [2018] likewise found in their survey that the vast majority of readers of scientific blogs were either pursuing or engaged in a science-related career.…”
Section: Core Group Of Active Commenters With Assumed Male Namesmentioning
confidence: 95%
“…SS had more pseudonyms compared to those clearly identified as male and JN had a majority of commenters who had assumed male names. In their survey of science blog readers, Jarreau and Porter [2018] also found that the majority (55%) reported being male, which compared to 37 per cent identifying as female (the rest did not answer or identify as one of these sexes). More of the commenters from SS used formal, technical language compared to JN commenters who were more likely to engage in short quotes using colloquial language.…”
Section: Core Group Of Active Commenters With Assumed Male Namesmentioning
confidence: 99%
See 2 more Smart Citations